Factors associated with antenatal care adequacy in rural and urban contexts-results from two health and demographic surveillance sites in Vietnam - Tran Toan K; Gottvall Karin; Nguyen Hinh D; Ascher Henry; Petzold Max (BMC, 2012)
Abstract Background Antenatal Care (ANC) is universally considered important for women and children. This study aims to identify factors, demographic, social and economic, possibly associated with three ANC indicators: number of visits, timing of visits and content of services. The aim is also to compare the patterns of association of such factors between one rural and one urban context in northern Vietnam. Methods Totally 2,132 pregnant women were followed from identification of pregnancy until birth in two Health and Demographic Surveillance Sites (HDSS). Information was obtained through quarterly face to face interviews. Results Living in the rural area was significantly associated with lower adequate use of ANC compared to living in the urban area, both regarding quantity (number and timing of visits) and content. Low education, living in poor households and exclusively using private sector ANC in both sites and self employment, becoming pregnant before 25 years of age and living in poor communities in the rural area turned out to increase the risk for overall inadequate ANC. High risk pregnancy could not be demonstrated to be associated with ANC adequacy in either site. The medical content of services offered was often inadequate, in relation to the national recommendations, especially in the private sector. Conclusion Low education, low economic status, exclusive use of private ANC and living in rural areas were main factors associated with risk for overall inadequate ANC use as related to the national recommendations. Therefore, interventions focussing on poor and less educated women, especially in rural areas should be prioritized. They should focus the importance of early attendance of ANC and sufficient use of core services. Financial support for poor and near poor women should be considered. Providers of ANC should be educated and otherwise influenced to provide sufficient core services. Adherence to ANC content guidelines must be improved through enhanced supervision, particularly in the private sector.